DOA DALAM GENGGAMAN: FENOMENA APLIKASI PENGINGAT IBADAH DI KALANGAN GEN Z - Fata Fata (Yayasan An-Nur Meunara Baro, 2025)
This study explores the phenomenon of prayer reminder applications among Generation Z within the context of digital religiosity transformation. The rapid advancement of digital technology, particularly smartphones, has introduced new forms of spiritual engagement, including